Jarak Parit Irigasi Jalur Untuk Tanaman Palawija Daerah Irigasi Banjarcahyana, Banjarnegara - Nastain Nastain (Jenderal Soedirman University, 2008)
At furrow irrigation, crops plant will use the root absorption capacity to keep taking water from trench, but, depth, spreading, and the root absorption capacity of furrow irrigation is limited, and depand crops species, age of crops, and soil caracteristic. Thus, the depth and trench distance planning is very important to determine productivity of crops plant. This research aimed to know effectivity of depth and trench distance at furrow i rrigation of Banj arcahyana irrigation system using water balance model. The result of research showed that trench distance has variative and depand on water level of trench and crops species. Melon needs more short trench distance than the other crops plant, where as the maximum requirement of water will occur on August and September.